Reference-dependent preferences and loss aversion - Einat Neuman; Shoshona Neuman (Judgment and Decision Making, 2008)
This study employs a Discrete Choice Experiment (DCE) in the health-care sector to test the loss aversion theory that is derived from reference-dependent preferences: The absolute subjective value of a deviation from a reference point is generally greater when the deviation represents a loss than when the same-sized change is perceived as a gain. As far as is known, this paper is the first to use a DCE to test the loss aversion theory. A DCE is a highly suitable tool for such testing because it estimates the marginal valuations of attributes, based onextit{ deviations from a reference point} (a constant scenario). Moreover, loss aversion can be examined for extiteach attribute separately. Another advantage of a DCE is that is can be applied toextit{ non-traded goods with non-tangible attributes}. A health-care event is used for empirical illustration: The loss aversion theory is tested within the context of preference structures for maternity-ward attributes, estimated using data gathered from 3850 observations made by a sample of 542 women who had recently given birth. Seven hypotheses are presented and tested. Overall, significant support for behavioral loss aversion theories was found. %JEL codes: D01, D12, I19